Using process evaluation for program improvement in dose, fidelity and reach: the ACT trial experience - Kitzman-Ulrich Heather; Saunders Ruth P; Griffin Sarah; Wilson Dawn K; Meyers Duncan C; Mansard Leslie (BMC, 2009)
Abstract Background The purpose of this study was to demonstrate how formative program process evaluation was used to improve dose and fidelity of implementation, as well as reach of the intervention into the target population, in the "Active by Choice Today" (ACT) randomized school-based trial from years 1 to 3 of implementation. Methods The intervention integrated constructs from Self-Determination Theory and Social Cognitive Theory to enhance intrinsic motivation and behavioral skills for increasing long-term physical activity (PA) behavior in underserved adolescents (low income, minorities). ACT formative process data were examined at the end of each year to provide timely, corrective feedback to keep the intervention "on track". Results Between years 1 and 2 and years 2 and 3, three significant changes were made to attempt to increase dose and fidelity rates in the program delivery and participant attendance (reach). These changes included expanding the staff training, reformatting the intervention manual, and developing a tracking system for contacting parents of students who were not attending the after-school programs regularly. Process outcomes suggest that these efforts resulted in notable improvements in attendance, dose, and fidelity of intervention implementation from years 1 to 2 and 2 to 3 of the ACT trial. Conclusion Process evaluation methods, particularly implementation monitoring, are useful tools to ensure fidelity in intervention trials and for identifying key best practices for intervention delivery.